The Relationship Between Human Resource Management and Organizational Performance - Renata Peregrino de Brito; Lucia Barbosa de Oliveira (BBR: Brazilian Business Review)
This paper presents a theoretical and empirical analysis of the relationship between human resource management (HRM) and organizational performance. Theoretically, we discuss the importance of HRM for the development of resources and its impact on business performance. Empirically, we evaluated articles published on Brazilian academic journals that addressed such relationships. The results showed a lack of studies conducted at this intersection. From the universe of 2,469 articles, only 16 (0.6%) sought to relate HRM and organizational performance. We observed a dominance of isolated HR practices, which does not consider HRM as a system, and of operational performance measures, relative to financial and efficiency variables. Most studies show a positive relationship between HRM practices and performance, in line with the literature. However, we point out some methodological issues, such as the difficulty of isolating the HR practices from its context, the failure to consider the temporality of this relationship, and the comparison between companies from different industries.